ANALISIS LAPORAN KEUANGAN PSAK NO.109 AKUNTANSI ZAKAT, INFAQ, DAN SHADAQAH (ZIS) (STUDI KASUS BADAN AMIL ZAKAT NASIONAL) - Arief Fadilah; Isro’iyatul Mubarokah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
It is anticipated that all BAZ/LAZ/OPZ will be equipped with PSAK 109 following its mandate on January 1, 2009.can put its financial reports into use.This study looked at the accounting reports for Zakat, Infak, and Shodaqoh (BAZNAS) to see if they had implemented PSAK 109 in 2009.The National Amil Zakat Agency of the Republic of Indonesia served as the sample for this study.The PPID BAZNAS RI website's financial reports from 2009 to 2021 served as the basis for the collection of secondary data.According to the findings, BAZNAS did not use the financial accounting report structure specified in the Statement of Financial Accounting Standards No.109 for shodaqoh, infaq, and zakat.BAZNAS makes financial reports like balance reports, sources and uses of funds reports, cash flow reports, and notes to financial statements public as evidence of this.cash flow reports, statements of financial position, fund movements, asset movements, and more.Notes to budget summaries should be in every way remembered for a coordinated PSAK 109 monetary report.It only conformed to PSAK in 2012, and even then, it lacked the same level of detail as the financial statements for 2016 to 2021.